The Effect of Extract of Red Pomegranate (Punica granatum Linn) on The Number of Macrophages of Ulser Traumatic of Rat Model - Sri Hernawati; Vinda Magdalena Drajat Mukhdaroh; Leni Rokhma Dewi (Humanistic Network for Science and Technology (HNST), 2023)
Therapy for traumatic ulcers using steroid causes serious side effects. Red pomegranate (Punica granatum Linn) can be used as alternative therapy which contains bioactive elements to reduce the number of macrophages in traumatic ulcers. The aimed of this study was to determine the potential of red pomegranate extract to reduce the number of macrophages in the rat model of traumatic ulcers. The 24 model rats were experimented within 3 groups including 8 animals each group (negative control using CMC-Na placebo, positive control using triamcinolone acetonide 0.1%, and treatment group using red pomegranate extract gel). Each group was divided into two (4 animals with a 3-day test and 4 animals with a 5-day test). Thermal-induced trauma was given to the labial mucosa of rats and then observing the number of macrophages histologically with 400x microscope magnification. The mean macrophages counted on the 3-day-tested groups of red pomegranate extract gel therapy, triamcinolone acetonide 0.1% therapy, and CMC-Na placebo therapy were 9.1, 16.5, and 22.3. While on the 5-day-tested groups, the mean of macrophages counted were 27.2, 23.6, and 28.9. In conclusion, red pomegranate extract had a significant effect in decreasing the number of macrophages in the inflammatory reaction of traumatic ulcer. Keywords: red pomegranate; traumatic ulcer; macrophage; anti-inflammatory